2005
DOI: 10.1002/imhj.20033
|View full text |Cite
|
Sign up to set email alerts
|

Differential attachment responses of male and female infants to frightening maternal behavior: Tend or befriend versus fight or flight?

Abstract: Taylor and colleagues (2000) proposed that males tend to display fight or flight responses to threat while females are more likely to display affiliative "tend or befriend" responses. In light of this hypothesis, gender differences in infant attachment behaviors were examined in a sample of 65 lowincome mother-infant dyads, half of whom were referred to a home-based intervention service because of concerns about the quality of caregiving. Attachment behaviors were assessed in the Ainsworth Strange Situation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
2
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 25 publications
6
48
2
1
Order By: Relevance
“…More specifically, overall maternal disrupted communication predicted child punitive behavior, while maternal withdrawal in infancy predicted child caregiving behavior. The association between maternal withdrawal and child caregiving behavior is consistent with the prediction of Lyons-Ruth et al(2002) that infants of more withdrawn mothers would be more likely to develop caregiving behaviors, based on their continued attempts to approach their mothers in infancy (see David & Lyons-Ruth, 2005). Moss et al (2009) also observed that mothers of caregiving preschoolers often appeared quite passive and disengaged, showing a neutral or negative affective expression.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…More specifically, overall maternal disrupted communication predicted child punitive behavior, while maternal withdrawal in infancy predicted child caregiving behavior. The association between maternal withdrawal and child caregiving behavior is consistent with the prediction of Lyons-Ruth et al(2002) that infants of more withdrawn mothers would be more likely to develop caregiving behaviors, based on their continued attempts to approach their mothers in infancy (see David & Lyons-Ruth, 2005). Moss et al (2009) also observed that mothers of caregiving preschoolers often appeared quite passive and disengaged, showing a neutral or negative affective expression.…”
Section: Discussionsupporting
confidence: 77%
“…NICHD Early Child Care Research Network, 2001). Alternately, David and Lyons-Ruth (2005) found that maternal withdrawal evoked approach behavior in infancy, so that some infants of very withdrawing parents were classified secure rather than disorganized. Therefore, disturbed attachment in infancy may be less likely to be detected in this subgroup (see Lyons-Ruth et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Schoppe-Sullivan et al, 2006). Alertando para a necessidade de mais estudos neste domínio, diferenças de género tanto ao nível da incidên-cia das classificações de segurança e de insegurança (Barnett, Kidwell, & Leung, 1998), como ao nível dos comportamentos discretos exibidos na Situação Estranha (David & Lyons-Ruth, 2005) têm também sido registadas em estudos envolvendo populações de risco.…”
Section: Comportamento De Vinculação E Génerounclassified
“…'Unresolved' loss or trauma in parents is linked to a mental representation in the child of the parent being "frightened" or "frightening", resulting in a disoriented child response . In this scenario, parents are a simultaneous source of fear and comfort (David & Lyons-Ruth, 2005). As consequences, as measured by the SST the infant utilizes a confused 'freeze' or erratic response in adaptation to threat of separationrather than the usual fight or flight coping strategies (Ayoub, Fischer, & O'Connor, 2003).…”
Section: Introductionmentioning
confidence: 99%